Multiple minimum coverings of Kn with copies of K4 - e - Lindner C.C.,; Penfold Street, Anne, (Utilitas Mathematica, 1997)
This paper is the last of a trilogy completely solving the maximum packing and minimum covering problems for the complete graph on n vertices, Kn, with copies of K4-e, that is, the complete graph on four vertices with one edge missing.